The Effects Of Share Repurchase Announcements In Kuala Lumpur Stock Exchange - Mohamad, Jais; Chin, Jimmy Y.F. (Universiti Malaysia Sarawak, (UNIMAS), 2002)
Share repurchase was not allowed for Malaysian listed companies until September 197, when the Malaysian government pushed through parliament a proposal to amend the Companies Act of 1965 in order to allow listed firms to repurchase their own shares. The new provision was Section 67A, which was introduced via the Companies (Amendment) Act 1997 and was implemented on 1 September 1997. With the Kuala Lumpur Composite Index (KLCI) plunging from 1012.84 points in July 1997 to 477.57 in January 1998, the move provided an excellent opportunity for local firms to repurchase their own shares.